2004
DOI: 10.1104/pp.103.035659
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Physiology of Cluster-Root Carboxylate Synthesis and Exudation in Harsh Hakea. Expression of Phosphoenolpyruvate Carboxylase and the Alternative Oxidase

Abstract: Harsh hakea (Hakea prostrata R.Br.) is a member of the Proteaceae family, which is highly represented on the extremely nutrientimpoverished soils in southwest Australia. When phosphorus is limiting, harsh hakea develops proteoid or cluster roots that release carboxylates that mobilize sparingly soluble phosphate in the rhizosphere. To investigate the physiology underlying the synthesis and exudation of carboxylates from cluster roots in Proteaceae, we measured O 2 consumption, CO 2 release, internal carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
133
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 53 publications
(57 reference statements)
17
133
4
Order By: Relevance
“…Consistent with earlier results (Shane et al, 2004a), (1) anti-PEPC immunoblots of stage I root extracts revealed comparable amounts of immunoreactive p110 and p107 that comigrated with the purified, partially monoubiquitinated PEPC heterotetramer from germinating COS, whereas (2) a progressive loss of immunoreactive p110 in stages II to III was paralleled by increased levels of p107 such that the total amount of immunoreactive PEPC polypeptides remained relatively constant (Fig. 2B).…”
Section: Influence Of Proteoid Root Development On Pepc Subunit Composupporting
confidence: 78%
See 4 more Smart Citations
“…Consistent with earlier results (Shane et al, 2004a), (1) anti-PEPC immunoblots of stage I root extracts revealed comparable amounts of immunoreactive p110 and p107 that comigrated with the purified, partially monoubiquitinated PEPC heterotetramer from germinating COS, whereas (2) a progressive loss of immunoreactive p110 in stages II to III was paralleled by increased levels of p107 such that the total amount of immunoreactive PEPC polypeptides remained relatively constant (Fig. 2B).…”
Section: Influence Of Proteoid Root Development On Pepc Subunit Composupporting
confidence: 78%
“…Similarly, a 2-fold increase in SUS activity occurred during maturation of white lupin proteoid roots (Massonneau et al, 2001). The peak in SUS and PEPC activities at stage III of hakea proteoid root development correlates with their maximal rates of citrate and malate exudation (Shane et al, 2004a). By contrast, citrate synthase (CS) and malate dehydrogenase (MDH) activities remained relatively constant throughout development (except in senescing stage IV roots, where they showed a pronounced decline; Supplemental Fig.…”
Section: Influence Of Proteoid Root Development On Key Enzymes Of Orgmentioning
confidence: 99%
See 3 more Smart Citations